Biofortified Diets Containing Algae and Selenised Yeast: Effects on Growth Performance, Nutrient Utilization, and Tissue Composition of Gilthead Seabream (Sparus aurata) - Ferreira, Mariana; Ribeiro, Pedro C.; Ribeiro, Laura; Barata, Marisa; Domingues, Valentina F.; Sousa, Sara; Soares, Cristina; Marques, Alexandra; Pousão-Ferreira, Pedro; Dias, Jorge; Castro, L. Filipe C.; Marques, António; et al. (Frontiers in Physiology, 2022)
Efforts have been made to find natural, highly nutritious alternatives to replace fish meal (FM) and fish oil (FO), which can simultaneously promote fish health and improve the nutritional quality of fillets for human consumption. This study evaluated the impact of biofortified diets containing microalgae (as replacement for FM and FO), macroalgae (as natural source of iodine) and selenised yeast (organic source of selenium) on gilthead seabream growth, nutrient utilization, tissue composition and gene expression. A control diet (CTRL) with 15 % FM and 5.5 % FO was compared with three experimental diets (AD1, AD2 and AD3), where a microalgae blend (Chlorella sp., Tetraselmis sp. and DHA-rich Schizochytrium sp.) replaced 33 % of FM. Diet AD1 contained 20 % less FO. Diets were supplemented with Laminaria digitata (0.4 % AD1 and AD2; 0.8 % AD3) and selenised yeast (0.02 % AD1 and AD2; 0.04 % AD3). After feeding the experimental diets for 12 weeks, growth was similar in fish fed AD1, AD2 and CTRL, indicating that microalgae meal can partially replace both FM and FO in diets for seabream. But AD3 suppressed fish growth, suggesting that L. digitata and selenised yeast supplementation should be kept under 0.8 and 0.04 %, respectively. Despite lower lipid intake and decreased PUFAs bioavailability in fish fed AD3, compared to CTRL, hepatic elovl5 was upregulated resulting in a significant increase of muscle EPA+DHA. Indeed, fillets of fish fed AD2 and AD3 provided the highest EPA+DHA contents (0.7 g 100 g-1), that are well above the minimum recommended values for human consumption. Fish consuming the AD diets had a higher retention and gain of selenium, while iodine gain remained similar among diets. Upregulation of selenoproteins (gpx1, selk and dio2) was observed in liver of fish fed AD1, but diets had limited impact on fish antioxidant status. Overall, results indicate that the tested microalgae are good sources of protein and lipids, with their LC-PUFAs being effectively accumulated in seabream muscle. Selenised yeast is a good fortification vehicle to increase selenium levels in fish, but efforts should be placed to find new strategies to fortify fish in iodine.